Life on the urban fringe.: Policies, territories and actors at a subnational level (Desarrollo, Estado y Espacio, 2023)
Changes in the capitalist and peripheral organization of the production and distribution of goods and services are giving the territory an increasingly hybrid physiognomy. This finds in the urban fringe or peri-urban areas a privileged locus of observation. In them are deployed social relations that, traversed by new spatial arrangements, express novel attributes that question and/or challenge both state intervention guidelines and long-standing theoretical and methodological perspectives. This dossier of the Journal Desarrollo, Estado y Espacio problematizes these topics by recovering nine articles presented at the Third Conference of Urban and Territorial Studies of the Institute of Humanities and Social Sciences of the Litoral (UNL-CONICET) and the Seventh Conference of Researchers in Urban Social Policies meetings of the Faculty of Legal and Social Sciences of the National University of the Litoral that took place in November 2022 in the city of Santa Fe, Argentina.
Keywords: urban fringe State, social inequality, land rents, landscape; urban fringe; social inequality; land rents; landscape